The Social Dynamics of Islamic Philanthropy in Blood Donation: A Case Study in Bulukumba Dinamika Sosial Filantropi Islam dalam Donor Darah: Studi Kasus di Bulukumba - Awal, Muh.; Shadra, Yasser Mulla (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
This paper outlines the historical background and development of a community service movement initiated by the Government of Bulukumba Regency in the form of a blood donation campaign (sedekah darah) as an expression of social concern for the community. The program adopts the Asset-Based Community Development (ABCD) approach through observation, interviews, and active participation from medical personnel, institutional administrators, and the surrounding community. The primary objective is to assist patients in need of blood transfusions while raising awareness about the importance of blood donation and fostering social philanthropy. The activities are conducted in various locations such as hospitals, government offices, university campuses, and public spaces, in collaboration with the Indonesian Red Cross (PMI) Bulukumba, Baznas Bulukumba, universities across Bulukumba Regency, and other governmental institutions, following hygienic and standardized medical procedures. The results indicate a high level of institutional collaboration, involving 46 institutions and collecting approximately 3,871 bags of blood within 12 months. The novelty of this study lies in the integration of local cultural values, Islamic philanthropic principles, and the ABCD approach within the context of a regional blood donation movement. This contributes both theoretically and practically to the understanding of modern social philanthropy grounded in local wisdom and institutional synergy at the regional level.ABSTRAKTulisan ini menguraikan historisitas dan perkembangan gerakan pengabdian yang diinisiasi oleh Pemerintah Kabupaten Bulukumba dalam bentuk gerakan sedekah darah sebagai wujud kepedulian sosial terhadap masyarakat. Program ini menggunakan pendekatan Asset Based Community Development (ABCD), dengan metode observasi, wawancara, dan partisipasi aktif dari tenaga medis, pengurus lembaga, dan masyarakat. Tujuan utama kegiatan ini adalah membantu pasien yang membutuhkan transfusi darah sekaligus meningkatkan kesadaran akan pentingnya donor darah dan nilai filantropi sosial. Kegiatan dilaksanakan di rumah sakit, kantor pemerintah, kampus, dan ruang publik lainnya, bekerja sama dengan PMI Bulukumba, Baznas Bulukumba, perguruan tinggi se-Kabupaten Bulukumba, serta lembaga pemerintah lain, dengan prosedur medis yang higienis dan sesuai standar. Hasil kegiatan menunjukkan kolaborasi aktif dari 46 lembaga dan pengumpulan sekitar 3.871 kantong darah dalam 12 bulan. Novelty dari penelitian ini terletak pada penggabungan antara nilai-nilai lokal, prinsip filantropi Islam, dan pendekatan ABCD dalam konteks gerakan donor darah. Ini memperkuat kontribusi teoritis dan praktis dalam memahami dinamika sosial filantropi modern berbasis kearifan lokal dan sinergi kelembagaan di tingkat daerah.